Otonomi Daerah dan Kebijakan Anggaran (Desentralisasi Fiskal)(Akuntabilitas yang Komunikatif dalam Manajemen Publik) - Yummil Hasan (Universitas Islam Negeri Imam Bonjol Padang, 2010)
The implementation of budgetary policies (fiscal decentralization), the days of local autonomy and communicative accountable on public authorities always show the relationship or interaction with the established policy goals. Hence, the implementation of communicative akuntabiliutas on a Board/ Department/ Office will provide a positive impact on the performance of that agency. Based on the analysis conducted, we believe that with the communicative accountability to ensure the successful achievement of organizational goals. Managerial accountability communicative emphasis on efficiency and pengehematan use of funds, property, human resources, and other power sources. Then establish a continuous process such as planning and budgeting, enabling them to provide the best public services. Efficiency of resource management that the authority of a government agency is a key feature of communicative managerial accountability.